Vegetation structure and aboveground biomass of Páramo peatlands along a high-elevation gradient in the northern Ecuadorian Andes - Suárez, Esteban; Hribljan, John A.; Chimbolema, Segundo; Harvey, Katie; Triana, Victoria; Zurita, Juan E.; Jaramillo, Ricardo; Doskocil, Lenka G. (Frontiers in Plant Science, 2023)
The high-elevation peatlands of the Andes constitute a diverse environment that harbors large numbers of species and several types of plant communities along altitudinal, latitudinal, and environmental gradients. However, little is known about the structure and functioning of these ecosystems, including peatland vegetation types and their relative contribution to the production and accumulation of peat soils. In this paper we characterized the structure of peatland plant communities of the humid páramos of northern Ecuador by describing the distribution of plant growth-forms and their aboveground biomass patterns. Along an elevation gradient of 640 m we sampled vegetation in 16 peatlands and aboveground biomass in four peatlands. Three distinct peatland vegetation types were identified: High elevation Cushion peatlands, dominated by Plantago rigida and Distichia muscoides, Sedge and rush peatlands dominated by Carex spp. and Juncus spp., and Herbaceous and shrubby peatlands, with a more heterogenous and structurally complex vegetation. In terms of aboveground biomass, we found an 8-fold reduction in the higher peatlands compared to the lower sites, suggesting that the steep elevational gradients characteristic of Andean environments might be crucial in structuring the physiognomy and composition of peatland vegetation, either through its effects on temperature and other environmental factors, or through its effects on the age and development of soils. Additional studies are needed to evaluate the potential effects of temperature, hydrology, micro-topography, geological setting, and land-use, which are likely to influence vegetation patters in these peatlands.